Artificial intelligence, business and civilization : our fate made in machines - Kaplan, Andreas (New York, NY : Routledge, 2022)
"Artificial intelligence is shaking up economies around the world as well as society at large and is predicted to be either the best or worst thing to happen to humanity. This book looks at what exactly artificial intelligence is, how it can be classified, how it differentiates from other concepts such as machine learning, big data, blockchain, or the Internet-of-Things, and how it has evolved and might evolve over time. Providing a clear and unbiased picture of artificial intelligence, the book provides critical analyses of the advantages and disadvantages, opportunities and threats of AI progress for business and civilization. Solutions and possible directions of how humanity might deal with rapid development and evolutions will be given and discussed, and consider regulation, employment, ethics, education and international cooperation. Unlike existing literature, this book provides a comprehensive overview of AI based on detailed analysis and insight. Finally, several real-life examples from various sectors and industries, including for profit organizations, higher education, and government, will substantiate and illustrate the presented concepts, classifications, and discussions. This book is of interest to researchers, educators, students, and practitioners alike who desire to understand AI in its broad lines and discover the latest research and studies within the field"--
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Economic aspects; Business enterprises -- Technological innovations; Information technology -- Management; International relations -- 21st century; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Information Management